Super-exchange-induced high performance charge transport in donor–acceptor copolymers. Issue 13 (2nd March 2017) - Cheng, Changli; Geng, Hua; Yi, Yuanping; Shuai, Zhigang
Abstract : Super-exchange-induced charge transport is proposed in donor–acceptor copolymers, and the corresponding design strategy for high mobility polymers is put forward. Abstract : Based on the super-exchange (SE) model and first-principles computations, we demonstrate that donor–acceptor copolymers can intrinsically possess an ultra-small effective mass due to the SE effect, rationalizing the recent experimental demonstration of ultra-high charge mobility. With the increase of the SE coupling, the effective mass decreases correspondingly. For the first time, we report that the SE coupling for holes is determined by the dihedral angle between the donor and the acceptor moiety, HOMO charge density at the linkage site and the HOMO–LUMO gap of the bridge fragment. Thereby, we put forward a molecular design strategy for large SE coupling so as to obtain an ultra-small effective mass. Finally, by combining a variety of donor and acceptor groups, we predict that several D–A copolymers can potentially possess an ultra-low effective mass due to the long range SE effect, and are expected to be high charge mobility polymers.